Has the Mfecane a future? a response to the Cobbing critique - Omer-Cooper, J. D. (Journal of southern African studies, 1993)
In recent years Julian Cobbing has advanced a wide-ranging critique of the concept of the Mfecane in southern, central and east African history. The Mfecane, he has maintained, was in origin a colonial myth to conceal white wrong-doing and justify land expropriation. Revived by well-intentioned 'Africanist' historians in the 1960s the concept has subsequently been exploited to justify aspects of apartheid. Rather than being the accompaniments of institutional change in African societies, he maintains that the wars and upheavals of the period must be attributed to the effects of increased white demand for African labour expressed in the massive expansion of the Delagoa Bay slave trade and slave raiding for the Cape labour market by Griquas with missionary and official involvement in Trans Orangia, white traders in Natal, and British military forces in the Transkei. Examination of the evidence, however, shows that the expansion of the slave trade in Delagoa Bay came after the area had been affected by the spread of upheavals from the south and could not have been their cause. Evidence for large-scale slave raiding and trading by Griquas, missionaries, Natal traders and British military commanders likewise proves unsubstantiated. The bold new paradigm cannot be sustained. The debate has, however, raised important new questions, enlivened research in the area and ensured that the Mfecane will continue to occupy a prominent place in the developing historiography of southern Africa.